Chemical characteristics and essential nutrients of agroindustrial effluents in Malaysia - Habib, M. A. B.; Md. Yusoff, Fatimah; Phang, Siew Moi; Kamarudin, Mohd Salleh; Mohamed, Suhaila (Asian Fisheries Society, 1998)
Three major agroindustrial effluents, namely, palm oil mill effluent (POME), latex concentrate rubber effluent (LCRE) and standard Malaysian rubber effluent (SMRE), were analyzed for chemical characteristics and biochemical properties and their essential nutrients evaluated. All the three raw effluents were highly acidic and did not contain dissolved oxygen. The raw POME contained significantly (p<0.05) higher chemical oxygen demand (COD) than raw LCRE followed by SMRE, indicating a high load of organic nutrients in these effluents. Crude protein in raw SMRE and LCRE was significantly higher than that in raw POME. But crude lipids, carbohydrate and ash content of raw POME were found to differ significantly (p<0.05) from those of raw LCRE and SMRE. All the 11 essential amino acids were available in raw LCRE, SMRE and POME. The POME contained higher amounts of unsaturated fatty acids such as oleic acid (18: 1n-9), linoleic acid (18: 2n-6), linolenic acid (18: 3n-3) and arachidonic acid (20: 2n-6) than the other effluents. However, very little amounts of eicosapentaenoic acid (20: 5n-3) were available in POME only. All together, 27 essential minerals were detected by scanning electron microscope and 22 essential minerals, were quantified by Inductuvely Coupled Plasma Mass Spectrophotometer, among which, Fe, Zn, P, Mg, Mn, Ca, K, Cr, Co, Cu, S, Se, Al, Sn, B, Mo, V, Li and Pb were found to be significantly (p<0.01) higher in raw POME than in the other effluents.